Fostering Innovation and Creativity in the UAE Educational System: Examining the Role of Educational Leaders in High Schools - Almarzooqi, Alya (2024)
Fostering creativity and innovation in secondary education is considered as a crucial element for students’ holistic development. However, evidence shows that there is limited research and understanding as far as the relationship between principal leadership styles and the development of creativity and innovation within the context of the United Arab Emirates (UAE) is concerned. To contribute to this important area, the paper focuses on assessing the role of education leaders in developing innovation and creativity in the UAE secondary education system. The study is based on a systematic review of fourteen scholarly sources related to educational leadership within the UAE's secondary school system. By collecting and analyzing relevant research from both survey-based and semi-structured interviews studies, the paper looks to identify traces of influence and potential influence of educational leadership on creativity, innovation, teacher performance, and student outcomes. The findings show that, while no research specifically considered the impact of educational leadership on creativity and innovation, several research papers discussed mediating factors. School leaders were cognizant of what innovation in schools meant and particularly acknowledged the creative problem-solving facet of innovation, however, only about half of school leaders facilitated the implementation of UAE policy on innovation in their schools. The review also found that managerial support for creativity was likely to promote creativity and innovation in teaching and in learning, thus improving teacher performance and student learning outcomes to some extent. The transformational leadership came up as a potential leadership style that could promote innovation and creativity in secondary schools despite the gross misunderstanding of the approach by some school leaders. The paper also identified a number of barriers hindering educational leaders from implementing innovative and creative practices and some suggestions on how these might be mitigated. While the findings are quite useful, the paper has some limitations; especially related to the lack of primary data to understand the role of school leaders in fostering innovation and creativity.